EXPLORATORY ANALYSIS TO DEVELOP BATIK LIMBASARI AND ITS COMPETITIVE ADVANTAGE - Sanctita, Mutia Puri; Wandebori, Harimukti (Journal of Business and Management, 2017)
Abstract. Batik is one of the popular fashions in Indonesia which has been acknowledged by UNESCO as original cultural heritage from Indonesia. In certain regional such as Purbalingga city, there is original written batik named Batik Limbasari that had been claimed by Purbalinga government as competitive commodity in Purbalingga. Batik Limbasari industry had undergone the rise and the fall through its development. Michael Porter introduced the theory Diamond Model of nation competitiveness consists of four segments which are firm’s structure, demand condition, supporting industry, and factor condition. Through this research, the author analyzed the current condition of Batik Limbasari industry. The research has an objective to give clear figure of the industry conditions and come up with some steps or applicative strategies recommended in order to develop the current industry. This research had been conducted in qualitative method by doing in-depth structured interview with the batik artisan, government, and PokDarWis Limbasari with the validation methods of triangulation to draw the repetitive results from the respondents. Prior to analyzing the internal and external environment of Batik Limbasari industry by doing environmental scanning, SWOT analysis, and Porter’s Diamond Model analysis. The result of this research revealed Batik Limbasari industry was still lack behind in several points. The difficulties to do regeneration combined with the low level of innovation decreased the interest of batik fashion especially to youth. Then, the demand condition was low due to the lack of marketing activities. The findings urged Batik Limbasari industry to develop its business process to be more innovative and responsive to market, also to strengthen the current domestic market. The recommendations for regional innovation system that could help the industry also formulated for Purbalingga government. Keywords: Batik Industry, Batik Limbasari, Competitive Advantage, Purbalingga City, Strategic Management